Lost in multitasking: An exploration of Chinese university students’ in-class smartphone multitasking patterns using multiple approaches - Zhou, Yujie; Deng, Liping (Australasian Journal of Educational Technology, 2024)
Smartphone multitasking is prevalent in university classrooms, yet the nature and characteristics of this behavior have not been sufficiently understood. This empirical study explores in-class smartphone multitasking behaviors using diverse research approaches to achieve a more authentic and holistic understanding of this pervasive behavior. First, semi-structured interviews were conducted to investigate the prevalence of in-class smartphone use, the types of smartphone tasks that students engaged in, and the modes of smartphone multitasking. Experience-sampling method (ESM) was used to capture the frequency and duration of smartphone use. Subsequently, a questionnaire survey was applied to validate the data collected in the former stage. The results provide a detailed and comprehensive account of in-class smartphone multitasking behaviors, including its prevalence, task types, modes, frequency, and duration. These findings highlight the need for educational researchers and practitioners to consider this behavior from multiple perspectives and with a holistic approach.